UJI KELAYAKAN SUMBER AIR KONSUMSI DI DESA KOTA BANGUN II KECAMATAN KOTA BANGUN DARAT KABUPATEN KUTAI KARTANEGARA - Kuniati, Asih; Purwati, Sri; Jailani, Jailani; Pribadi, Teguh (BIOEDUKASI (Jurnal Pendidikan Biologi), 2024)
The water used by the community in Kota Bangun II Village for drinking and daily needs comes from three types of groundwater sources, namely natural sources, drilled wells and dug wells. This research aims to determine the suitability of the air consumed by the people of Kota Bangun II Village. This type of research is descriptive quantitative with the parameters tested being physical, chemical and biological parameters. The air sampling technique used in this research was purposive sampling. The air testing site at the Air Quality Laboratory and Microbiology and Aquaculture Biotechnology Laboratory, Faculty of Fisheries and Marine Sciences, Mulawarman University, research was carried out for 3 months, namely January-March 2023. Based on the research results which have been compared with PERMENKES No. 492 of 2010 and Indonesian Government Regulation no. 82 of 2001 and Government Regulation no. 20 of 1990 that the source of drinking water in Kota Bangun II Village cannot be consumed directly and does not qualify as standard water